C4-Selective Alkylation of Pyridines through Amidyl-Radical-Mediated 1,2-Hydrogen Atom Transfer - Ju, Hyewon; Tan, Chang-Yin; Hong, Sungwoo (Synlett, 2025)
Hydrogen atom transfer (HAT) reactions play a vital role in radical chemistry and biological systems, enabling selective C–H functionalization through bond dissociation energy and polarity effects. Whereas intramolecular 1,5-HAT is well established, 1,2-HAT processes remain relatively challenging, particularly for nitrogen-centered radicals, due to high activation barriers. Here, we report a successful 1,2-HAT of amidyl radicals generated from N-amidopyridinium salts, enabled by a frustrated Lewis pair system of t-Bu3P and the pyridinium salt, without requiring an external photocatalyst. The phosphine serves dual roles: reducing the pyridinium salt through single-electron transfer and facilitating the 1,2-HAT process under mild conditions. Visible-light irradiation enhances the reaction efficiency, allowing late-stage functionalization of pyridine-containing pharmaceuticals. This method offers a new approach to selective pyridine C–H functionalization, broadening the scope of HAT chemistry in synthesis.
Keywords: hydrogen atom transfer; pyridines; frustrated Lewis pair; late-stage functionalization; single-electron transfer; radical-chain reaction